PENGARUH JENIS ASAM DAN pH PELARUT TERHADAP KARAKTERISTIK PEKTIN DARI KULIT LEMON (Citrus limon) - Kesuma, Ni Kadek Yuli; Widarta, I Wayan Rai; Permana, I Dewa Gede Mayun (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 7 No 4 (2018): Jurnal ITEPA, 2018)
This research was conducted with the aim to know the influence of acid and solvent pH on the extraction of pectin from lemon peel and find the right kind of acid and solvent pH to produce pektin of lemon peel with the best characteristics. The experimental design used in this research was a factorial Completely Randomized Design (CRD), which consisted of two factors. The first factor was a type of acid consisting of chloride acid and citric acid. The second factor was a solvent pH consisting of a pH 1,5; 2; 2,5 and 3. All treatments were repeated twice to obtain 16 units of experiments. The data were analyzed with analysis of variance and followed by Duncan test. The best results showed that extraction using chloride acid and pH of solvent 1,5 resulted in 22,35% of pectin yield, 11, 55% of water content, 22,11% of ash content, 1052,47% of equivalent weight, 10,81% of methoxyl content, 78,07% of galacturonic content, and 78,58% of esterification degree.